ß-Carotene - S.F.Parker, ISIS (My University, 2017)
Inelastic Neutron Scattering spectrum of ß-Carotene, C₄₀H₅₆, measured on the TOSCA instrument. Type 1 glassy carbon (carbonization temperature is <1000 C)..
Keywords: TOSCA